TEST THE REACTION OF THE BANK SYARIAH INDONESIA STOCK MARKET (STUDY OF EVENTS PP MUHAMMADIYAH DECIDED TO WITHDRAW CUSTOMER FUNDS) - Sopian, Adi; Purnomo, Budi Supriatono; Purnamasari , Imas (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the differences in abnormal returns and trading volume activity before and after the announcement of the Muhammadiyah Central Leadership (PP Muhammadiyah) memo regarding the consolidation of member funds, which are not to be concentrated in Bank Syariah Indonesia (BSI). The research method used is an event study method with a paired sample t-test to assess the significance of differences between the periods before and after the announcement. The data utilized include abnormal returns and trading volume activity for 10 days before and after the event. The results of this study indicate no significant difference in abnormal returns before and after the announcement. This suggests that the PP Muhammadiyah memo did not affect stock returns, as shareholders still trust the credibility of BSI's management, disregarding external influences. However, in terms of trading volume activity, there is a significant difference between the periods before and after the announcement. This is due to a decline in trading volume after the announcement, as shareholders observe the situation of BSI stock trading before deciding to buy or sell shares.